PENGGUNAAN MEDIA JENGA DALAM MODEL TGT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJARDI SMPN 4 KOTA MALANG MATERI KEGIATAN EKONOMI MATA PELAJARAN IPS - Avinda Azizatun Nisa; Abdul Latif Bustami; Avinda Azizatun Nisa (Universitas Negeri Malang, 2024)
Abstract: This research aims to increase motivation and learning outcomes by using Jengamedia in teams’ games tournament (TGT) learning model. Students are lessenthusiastic about social studies because teachers’ learning is still traditional andmonotonous. This classroom action research was conducted in two cycles. Theresearch results showed that the data obtained from the learning motivationquestionnaire was at a sufficient level with an average score of 60.8 percent before theaction. Motivation to learn increased with an average score of 89.7percent in the highcategory. Meanwhile, for learning outcomes, the average pretest score was 63.8and increased to 79.1 afterthe action was given. This also proves that the use ofJenga media in the TGT model can also increase the motivation and learningoutcomes of class 7H students at SMPN 4 Kota Malang.